(untitled) (Research, Society and Development, 2023)
We estimated the prevalence of screening for prostate cancer in indigenous people in Brazil. We also studied how ethnicity, age, social conditions, lifestyle, and history of sexually transmitted infections are associated with altered prostate-specific antigen (PSA) values. This is a cross-sectional study with indigenous people, ≥ 40 years old, from Dourados reserve, Mato Grosso do Sul, Brazil. The patients underwent total PSA and rapid tests for syphilis, HIV, and hepatitis B and C. PSA values were compared with sociodemographic conditions, presence of urological symptoms, clinical data on sexually transmitted infections, lifestyle, and family history of cancer. Out of the 498 men invited to participate in the study, 31.53% (157/498) were ≥ 40 years old and were included. The mean (±SD) age was 54.75 (±11.23) years, and 78.3% (123/157; 95% CI: 0.71–0.84) of the population never underwent any preventive examination for prostate cancer. The mean PSA value was 0.081 ng/mL for the 157 participants, and 4.4% (7/157) had > 2.5 ng/mL and 1.9% (3/157) had values ≥ 4 ng/mL. Rapid tests for STIs showed that 5.73% (9/157) of the participants had syphilis and 0.64% (1/157) had HIV, and Hepatitis B and C virus infection. The results showed that most indigenous people ≥ 40 years never underwent any preventive examination for prostate cancer, and 4.4% had an altered PSA exam result. Future studies should assess the factors that hinder adherence to prostate cancer screening, as well as the existence of a pathophysiological correlation between the occurrence of prostate cancer and STIs.